Transnational legal activism in global value chains : the Ali Enterprises Factory fire and the struggle for justice - Saage-Maass, Miriam; Zumbansen, Peer, 1966-; Bader, Michael; Shahab, Palvasha (Springer, 2021)
This open access book documents and analyses the various interventions legal, political, and even artistic that followed the Ali Enterprises factory fire in Karachi, Pakistan, in 2012. It illuminates the different substantive and procedural aspects of the legal proceedings and negotiations between the various local and transnational actors implicated in the Ali Enterprises fire, as well as the legal and policy reforms sparked by the incident. This endeavour serves to embed these legal cases and reform efforts in the larger context of human and labour rights protection and global value chain governance. It also offers a concrete case study relevant for ongoing debates around the role of transnational approaches in making human rights litigation, advocacy, and law reform more effective. In this regard, the book interrogates and critically reflects on such legal campaigns and local and transnational reform work with a view to future transformative legal and social activism.
Keywords: Employee rights -- Pakistan.; Human rights -- Pakistan.; International law and human rights.; Personnel -- Droits -- Pākistān.; Droits de l'homme (Droit international) -- Pākistān.; Droit international et droits de l'homme.; Employee rights; Human rights; International law and human rights; Pakistan